Environments at the MIS 3/2 transition in the northern Alps and their foreland - Stojakowits, Philipp; Mayr, Christoph; Ivy-Ochs, Susan; Preusser, Frank; Reitner, Jürgen M.; Spötl, Christoph (Quaternary international, 2020)
This paper reviews the current state of knowledge about environmental changes at the MIS 3/2 transition in the northern Alps and their foreland, covering the time frame from 35 to 25 ka. Lake and peat deposits, cave sediments, loess and glacial deposits are presented and the response of their biotic and abiotic proxies to climate change is discussed. During late MIS 3, interstadial conditions, albeit weak, occurred at c. 36–32 ka. At climatically favourable sites, small patches of trees (mainly Pinus and some Betula) existed together with some shrubs. The environmental conditions during late MIS 3 are also reflected by a boreal brown soil horizon, a cambisol called Lohne soil, found in many loess sequences. Subsequently, the environmental conditions became harsher as shown by the proxy data. From c. 30 ka onwards the absence of pedogenesis sensu stricto and the plant assemblages point to an Arctic climate in the northern Alpine foreland. Accentuating, glaciers advanced beyond the northern limit of the Alps around the MIS 3/2 boundary and reached their maximum extent in the foreland at about 25 ka.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Last glacial maximum; Molluscs; Palaeo-environment; Palaeosol; Vegetation response